Controllable synthesis and characterization of Mg2SiO4 nanostructures via a simple hydrothermal route using carboxylic acid as capping agent and their photocatalytic performance for photodegradation of azo dyes. Issue 35 (18th June 2021) - Moshtaghi, Saeed; Hamadanian, Masoud; Amiri, Omid; Goli, Maryam; Salavati-Niasari, Masoud
Abstract : Mg2 SiO4 nanostructures have been synthesized via a facile hydrothermal approach. The photocatalytic behavior of Mg2 SiO4 nanostructures prepared by different carboxylic acids have been investigated to degrade azo dyes under UV and visible light. Abstract : Magnesium silicate (forsterite) nanoparticles were synthesized by a facile hydrothermal method, and characterized using several techniques such as XRD, SEM, EDS, DRS, Raman, TEM, and FT-IR. Several carboxylic acid structures were applied to modify the morphology and surface properties of the as-prepared particles. In this manuscript, citric acid, maleic acid, and succinic acid were used as the carboxylic acid agents. The effect of changing the ratio of carboxylic acid agent to central metal on the morphology and photocatalytic behavior was evaluated. The activities of the Mg2 SiO4 nanostructures as photocatalysts were assessed by the degradation of several azo dyes (Acid Blue 92, Acid Brown 14, and Acid Violet 7) under UV and Vis light irradiation. The degradation percentages of Acid Blue 92 were about 88% and 74% in the presence of Vis and UV light respectively, and the percentages for photodegradation of Acid Brown 14 were approximately 76% and 82% in the presence of Vis and UV light, respectively. Furthermore, the degradation percentages for Acid Violet 7 were 93% and 80% under UV and Vis light, respectively.